Nubian textile features: Wool fragments from Hisn al-Bab and a tunic from Fag el-Gamus, Egypt - Kwaspen, Anne (Archaeological Textiles Review, 2021)
Excavations carried out by the Cairo Branch of the Austrian Archaeological Institute since 2012 at the site of Hisn al-Bab, a military settlement 10 km south of Aswan in Egypt, revealed an abundance of textile fragments dating from the late sixth to early seventh centuries CE. A study group of 80 textiles was selected of which 60 wool examples were analysed and compared with wool textiles from Lower Nubia and Egypt. Research into the typical features of Nubian textiles also led to the discovery of what may be an exceptional Nubian wool tunic unearthed at the cemetery of Fag el-Gamus at Fayum in Egypt.